2019
DOI: 10.1021/acs.accounts.8b00641
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Iodinated Disinfection Byproducts (I-DBPs) in Drinking Water: Emerging Concerns and Current Issues

Abstract: CONSPECTUS: Formation of iodinated disinfection byproducts (I-DBPs) in drinking water has become an emerging concern. Compared to chlorine-and bromine-containing DBPs, I-DBPs are more toxic, have different precursors and formation mechanisms, and are unregulated. In this Account, we focus on recent research in the formation of known and unknown I-DBPs in drinking water. We present the state-ofthe-art understanding of known I-DBPs for the six groups reported to date, including iodinated methanes, acids, acetami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(91 citation statements)
references
References 72 publications
2
89
0
Order By: Relevance
“…However, the formation of I-THMs in the raw water sample is not correlated to the treated waters with much higher I-THMs formed than the correlation with the 4 treated water would have predicted. The content of ammonia in the water (as chloramines favours I-DBP formation compared to chlorine 39 ) does not explain this behaviour either as the raw water shows the same concentration as the waters treated by the IRA-410 and IRA-958 resins (around 0.17 mg L -1 ) and a lower concentration than the waters treated by PPA860S and TAN-1 resins (around 0.27 mg L -1 ). Then, the removal of NOM DBP precursors is a key factor in the control of I-DBP formation.…”
Section: I-thm24hmentioning
confidence: 94%
“…However, the formation of I-THMs in the raw water sample is not correlated to the treated waters with much higher I-THMs formed than the correlation with the 4 treated water would have predicted. The content of ammonia in the water (as chloramines favours I-DBP formation compared to chlorine 39 ) does not explain this behaviour either as the raw water shows the same concentration as the waters treated by the IRA-410 and IRA-958 resins (around 0.17 mg L -1 ) and a lower concentration than the waters treated by PPA860S and TAN-1 resins (around 0.27 mg L -1 ). Then, the removal of NOM DBP precursors is a key factor in the control of I-DBP formation.…”
Section: I-thm24hmentioning
confidence: 94%
“…Iodide is present naturally in ground water, but concentrations are incremented by anthropogenic activities, including improper disposal of iodinated wastes, and release of iodide-containing pharmaceuticals. These increased environmental concentrations are usually linked to undesirable effects in wastewater treatment plants generating iodinated disinfection by-products (I-DBPs) (Dong et al, 2019;Duirk et al, 2011;Hapeshi et al, 2013;Kormos et al, 2010). For example, the use of oxidizing agents like chlorine, chloramine, ozone (Tian et al, 2013;Weinberg et al, 2002) or potassium permanganate (Ye et al, 2012), promotes oxidation of iodide anion to hypoiodous acid, which acts as a precursor, reacting with organic matter to generate I-DBPs.…”
Section: Figmentioning
confidence: 99%
“…For example, the use of oxidizing agents like chlorine, chloramine, ozone (Tian et al, 2013;Weinberg et al, 2002) or potassium permanganate (Ye et al, 2012), promotes oxidation of iodide anion to hypoiodous acid, which acts as a precursor, reacting with organic matter to generate I-DBPs. Such compounds are incorporated in drinking water at concentrations from ng/L to μg/L and ingested by humans directly (drinking water) or indirectly (cooking water) (Dong et al, 2019), alongside iodinated table salt, making calculation of exposure problematic (Becalski et al, 2006;Pan et al, 2016). Recently reviewed by Dong et al (2019), iodinecontaining compounds can be present as iodinated methanes, iodo-acids, iodo-haloacetamides, iodo-haloacetonitriles, iodo-haloaldehydes and iodo-phenols.…”
Section: Figmentioning
confidence: 99%
“…As assessed by Richardson et al (2008) in chlorinated and chloraminated drinking waters from 23 cities in the U.S. and Canada, as well as reviewed by Postigo and Zonja (2019) and Dong et al (2019), various I‐DBPs have been found in drinking water during the disinfection of waters containing iodide and/or organic iodine. The types and concentrations of I‐DBPs are influenced by the concentration of iodide (Richardson et al, 2008; Jones et al, 2012; Postigo et al, 2017), the molecular size of the natural organic matter (NOM) (Zhang et al, 2016), and the presence of iodinated X‐ray contrast media in the source water (Duirk et al, 2011; Wendel et al, 2014; Xu et al, 2017; Postigo et al, 2018; Ackerson et al, 2020).…”
Section: Introductionmentioning
confidence: 97%